Advances in intelligent systems for defence - Jain, L. C.; Ichalkaranje, Nikhil; Tonfoni, G. (Series on innovative intelligence ;, 2002)
This work reflects on trends in milirary information systems research by bringing together international contributions that span communications technology, intelligent agents and large-scale modelling and simulation, and sociotechnical systems.